The Role of Civics Learning in Facilitating the Development of Anti-Bullying Characters in Elementary Schools - Padli Prasitya, Ahmad; Linda Atika Dewi; M Risdamuddin (International Journal of Basic Educational Research, 2025)
This study aims to analyze the strategic role of Civic Education (Pendidikan Kewarganegaraan or PKn) in shaping students’ character at the elementary school level, with a particular focus on instilling anti-bullying values, strengthening interpersonal relationships, and preventing as well as intervening in bullying behavior. The research addresses the growing concern over school bullying, which negatively affects students’ emotional well-being and social development. By exploring how PKn can serve as a medium for moral and ethical education, this study contributes to both the theoretical understanding and practical implementation of character education in elementary schools. The research was conducted at SDN Kowangbinagun using a qualitative approach with a case study design. Data were collected through observations, in-depth interviews with teachers and students, and documentation of school activities. The collected data were analyzed using Miles and Huberman’s model, which consists of data reduction, data display, and conclusion drawing/verification. This method ensured that the findings were systematically derived from field data. The study found that PKn plays a crucial role in promoting moral values such as empathy, responsibility, tolerance, and justice among students. Through interactive teaching methods, including group discussions, reflection activities, and collaborative tasks, students developed improved interpersonal skills, including assertive communication and conflict resolution. PKn also effectively functioned as a preventive and intervention tool against bullying, as teachers actively provided awareness, corrected negative behaviors, and fostered a safe and supportive school environment. This study concludes that PKn serves as an effective instrument in cultivating a respectful, empathetic, and cooperative school culture, which ultimately reduces bullying incidents. Future research may explore the integration of digital tools in PKn learning to enhance character education outcomes.